Angiogenesis-a novel therapeutic approach for ischemic heart disease - Nessa, Akhtarun; Latif, SA; Siddiqui, NI; Hussain, MA; Bhuiyan, MR; Hossain, MA; Akther, A; Rahman, M (Mymensingh Medical Journal, 2009)
Mymensingh Med J. 2009 Jul;18(2):264-72. The abstract of this article is available on the PubMed website